2009
DOI: 10.1007/s11199-009-9658-9
|View full text |Cite
|
Sign up to set email alerts
|

She’s Got the Look: Inferences from Female Chief Executive Officers’ Faces Predict their Success

Abstract: Inferences from faces can predict success. This may be particularly important for women, who are often evaluated by their appearance. Here 170 northeastern U.S. undergraduates judged personality traits or leadership ability from the faces of all 20 U.S. Fortune 1,000: 2006 female chief executive officers (CEOs) and we compared these ratings to the same trait ratings made for male CEOs in a previous study. After controlling for cues important for female leaders (attractiveness, affect, age, and masculinity/ fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 30 publications
6
68
0
Order By: Relevance
“…As Lefevre et al (2013) have suggested, it is plausible that women's facial characteristics are entirely different than men's. Though it is important to note that neither assessed fWHR, at least two other studies have shown that women's faces reveal aspects of their dominance and aggressive behavior (Quist et al 2011;Rule and Ambady 2009). This presents the possibility that additional facial markers might indicate women's formidability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As Lefevre et al (2013) have suggested, it is plausible that women's facial characteristics are entirely different than men's. Though it is important to note that neither assessed fWHR, at least two other studies have shown that women's faces reveal aspects of their dominance and aggressive behavior (Quist et al 2011;Rule and Ambady 2009). This presents the possibility that additional facial markers might indicate women's formidability.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown that certain aspects of women's behavior can be accurately assessed from their faces, but none have included an fWHR measurement. For example, after controlling for age, facial expression, and attractiveness and masculinity ratings, Rule and Ambady (2009) showed that female chief executive officers who were rated as having higher leadership quality were more likely to have led companies with higher annual profits, and those who were rated as more dominant earned higher salaries, but the facial features raters used to make these judgments was not assessed. Similarly, Quist et al (2011) showed that women who scored higher in self-reported dominance had faces that were rated as more masculine, but they did not assess which facial markers were used to make these assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In each block, participants saw all 92 faces presented in random order. The order of the blocks was random and each block consisted of a different trait judgment: competence, dominance, facial maturity, likeability, and trustworthiness (see Rule & Ambady, 2008, 2009. Each trait was rated along a 7-point scale, anchored at 1 "Not at all X" to 7 "Very X".…”
Section: Methodsmentioning
confidence: 99%
“…One particularly relevant component may be the expression of dominance, which plays an important role in establishing status hierarchies among primates (e.g., Mazur, 2005). Interestingly, in two previous studies, CEOs who looked more dominant and powerful were associated with companies that earned more profits (Rule & Ambady, 2008) and individual compensation (Rule & Ambady, 2009). One explanation for this could be that CEOs who look like better leaders or who look more dominant might be hired by more successful companies.…”
mentioning
confidence: 93%
See 1 more Smart Citation